Análisis económico del cultivo de arroz en la coopertativa de producción y comercialización agrícola guayacanes del canton Arenillas - Noblecilla Sánchez, José Javier (2012)
His study was conducted in the Production and Marketing Cooperative "Guayacanes", it maintains its headquarters in the town of Guayacanes, belonging to the canton Arenillas there of having its inception on March 1of the Ministerial Registration and ripped 2001 mediate with 37 members, of whom developed a direct interview 20 producers of which 17weredevotedtotheexploitation office cultivar.The cultivation is do new it preparing the ground with the help of agricultural machinery in the area, and planting is done directly by scattering, to give the respective care in relation to weed control, nutrition, plant protection.The harvest is performed with the aidof machinery and is transported to the postharvest process, of which there is an average of 80 quintals per hectare milled rice.The marketing is do nein most intermediary es at a cost of 29,72andthecost of production per hectares $. 1 757,59 for which’s hound produce an amount of 59,13 quintals to covert these expenses.